Joint optimal PMU and DULR placement in distribution network considering fault reconstruction and state estimation accuracy - Wu, Zhi; Jiang, Jiachen; Zheng, Shu; Zhao, Jingtao; Gu, Wei (International journal of electrical power & energy systems, 2024)
•This paper proposes a joint optimal placement model for PMU and DULR to minimize costs while ensuring accuracy of SE and the rate of load loss after fault.•A new two-step state estimation method considering both sides of the mixture is used to solve the part of state estimation in the joint optimal distribution method proposed in this paper, which ensures the accuracy of the calculation results and improves the calculation efficiency.•The optimal solution of the optimal placement was obtained by solving the mixed integer semidefinite programming (MISDP) problem.•The results of joint optimization for point placement depend on the number of FTU, DG, and tie line configurations, as well as the consideration of multiple fault scenarios. Incorporating these scenarios enhances the configuration efficiency of PMU and DULR, while FTU, DG, and tie lines help reduce overall configuration costs. Due to the rapid development of the distribution network, there is an urgent need for high-precision state estimation and safe and stable operation, this paper proposes a joint optimal placement method for Phasor Measurement Unit (PMU) and Dual Use Line Relay (DULR) in distribution networks considering fault reconstruction and state estimation accuracy. The proposed method aims to minimize the cost of PMU and DULR configuration. Based on the known pseudo-measurements and Supervisory Control and Data Acquisition (SCADA) measurements, we use the E-optimal standard design of the state estimation error covariance matrix to form the state estimation accuracy index and take the relay protection function of Feeder Terminal Unit (FTU) device and DULR device into consideration of the fault reconstruction. By solving the mixed integer semidefinite programming (MISDP) model, the optimal placement result is obtained, so that the network under normal condition and the network after multiple fault reconstruction can meet the constraints of state estimation accuracy and load loss rate respectively. The proposed method is tested on IEEE 33-node, 123-node systems as an example. The experimental results show that the proposed method is effective and practical. Note to Practitioners—This study is stimulated by the need for optimizing the placement of Micro-PMU (µPMU) in distribution network. Since the new µPMU device DULR has the same relay protection function as FTU, and distributed generation can supply power to the island after failure, this paper adds the load loss rate to the constraint conditions to study the influence of fault reconstruction on the placement scheme. A new two-step SE method considering mixed measurements was used in this paper to improve the computational efficiency of real-time SE of large-scale system while ensuring the accuracy of the calculation results. We have conducted tests in IEEE-33 and IEEE-123 systems. After preliminary verification, compared with the single fault scenario, we find that the placement scheme considering multiple fault scenarios can effectively improve the accuracy of state estimation and reduce the load loss rate of each fault scenario and only increase the cost a little. The increase in the number of DG and contact lines in the network will also effectively improve the feasibility of the placement scheme. The increase of the number of FTU configurations can effectively reduce the configuration of DULR by adding a small amount of µPMU, reduce the total cost as a result. In future studies, we will further consider the integrated configuration of µPMU, DULR and FTU, to meet more failure scenarios while reducing costs.